Cadaveric Evaluation of Dorsal Intermetatarsal Approach for Plantar Plate and Lateral Collateral Ligament Repair of the Lesser Metatarsophalangeal Joints. (July 2017) - Phisitkul, Phinit; Hosuru Siddappa, Vinay; Sittapairoj, Tinnart; Goetz, Jessica E.; Den Hartog, Bryan D.; Femino, John E.
Background: Access to the plantar plate has been described using either a plantar approach or an extensive dorsal approach that required complete joint destabilization and often a metatarsal osteotomy. Clinical scenarios related to plantar plate tear vary and the pathologies in early stages are frequently limited to unilateral soft tissue structures; a less invasive operative approach may be possible. A novel approach requiring a release of only the lateral collateral ligament and the lateral half of the plantar plate is presented in this cadaver model; the extent of joint exposure possible is described. The ability to place a secure suture through the lateral collateral ligament and the plantar plate was analyzed. Methods: Nine fresh-frozen cadaveric specimens were dissected in a randomized fashion across the second to fourth metatarsophalangeal joints through the intermetatarsal space dorsally. Under distraction, soft tissue was sequentially released, including dorsal capsule, lateral collateral ligament, and the lateral half of the plantar plate. Integrity of the extensor tendons, deep transverse intermetatarsal ligament, proximal attachment of the plantar plate, and osseous structures was carefully preserved. The joint exposure was quantified after each step with sizing rods. Using a suture passer, 2-0 nonabsorbable braided sutures were passed into the lateral collateral ligament and the plantar plate, and the construct strength was measured using a tensiometer. Results: Progressive increase in mean joint exposure was noted after each step of soft tissue release with the final exposure of 6 mm after release of the lateral half of the plantar plate. Joint exposures after a capsulotomy and a lateral collateral release were 3 mm and 4 mm, respectively. Under distraction, the unilateral release of soft tissue created a lateral opening of the joint while the proximal phalangeal base adducted and medially deviated. Successful suture passage was noted in all specimens that could sustain a minimum tension of 25 N without a catastrophic failure. There was no statistically significant correlation with age, sex, foot length, and rays of the specimens when joint exposure was considered. Conclusion: The dorsal intermetatarsal approach appeared to be feasible for access to the lateral collateral ligament and the lateral half of the plantar plate. The average joint exposure of 6 mm allowed a quality suture passage by a suture passer in both structures in all specimens without the need of a metatarsal osteotomy. Clinical relevance: This operative approach may be appropriate for early stages plantar plate tear when only lateral soft tissue repair is needed. This technique should not preclude conversion to a more extensile operative approach or an additional metatarsal osteotomy if needed. Applicability of this operative approach in cases with more advanced pathologies or involving only medial soft tissue structures requires further studies.